Degradasi Pewarna Methylene Blue (MB) Menggunakan Fotokatalis WO3/Fe2O3 dengan Perbantuan Cahaya Matahari - Widiyandari, Hendri; Syam, Burhanudin (JURNAL SAINS DAN MATEMATIKA, 2012)
Degradation of dangerous pollutant with photocatalyst under solar or visible light radiation was a smart solution for environment pollution complication specifically for wastewater. an efficient photocatalyst which works at under wide spectrum from solar radiation. We reported the of tungsten oxide/ferric oxide (WO3/Fe2O3) composite with 6 variant weight ratio Fe additve (0%, 2%, 4%, and 6%).. Methylene blue photodegradation result showed, the decrease intensity of C/C0 concentrationÂ more faster and constant especially for 6% additive co-catalyst Fe. Then, the photodegradation sample has result more pure than 5 sample others. Â Keywords: WO3/Fe2O3, Photodegradation, photodeposition method, composite material, co-catalyst